DAYA TERIMA DAN ANALISIS KANDUNGAN SERAT PADA BROWNIES PANGGANG BERBAHAN DASAR TEPUNG SORGUM DAN TEPUNG KACANG MERAH - Anisa Triwahyuni (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2025)
Brownies are a popular cake among various groups of people. The main ingredient in brownies is wheat flour, which contains gluten and can potentially cause health problems such as celiac disease, gluten intolerance, autism, and has a low fiber content that can lead to weight gain, constipation, and the risk of diabetes mellitus. Therefore, there is a need for gluten-free and high-fiber product innovations. One alternative is sorghum flour and red bean flour as healthy food choices. This study aims to evaluate the acceptability of color, taste, aroma, texture, analyze the dietary fiber content, and determine the best formulation. This study used a non-factorial Complete Randomized Design (CRD) with 4 treatments in the form of sorghum flour and red bean flour proportions, namely F0 (control), F1 (1:3), F2 (1:1), and F3 (3:1). Data analysis used for acceptability was Kruskal Wallis with Mann Whitney follow-up test, dietary fiber content was one-way ANOVA with Tukey follow-up test, and the best formulation was determined using the exponential comparison method. Overall, the acceptability of color, taste, aroma, and texture was acceptable to the panelists, and the dietary fiber content was F0 (2.56%), F1 (3.93%), F2 (3.78%), and F3 (3.56%). The best formulation for baked brownies was formulation F2 (1:1) with an average color (4.02), taste (3.9), aroma (4.04), and texture (3.88) and contained 3.78% dietary fiber. Thus, baked brownies made from sorghum flour and red bean flour can produce a product with good nutritional value without reducing the panelists' level of preference.